A novel two degree-of-freedom ultrasonic planar motor driven by single stator - Yan, Liang (2013)
A novel two degree-of-freedom (DOF) ultrasonic planar motor based on traveling wave has been proposed in this paper. The stator is the key component of the planar motor. The proposed stator is in a bar type, consisting of three piezoelectric ceramic cylinders and a metal driving head. The effective elliptical motion of the driving head tip is formed by the second bending mode and the first longitude mode of the stator. The two working vibration modes are analyzed by FEM software, and the dimensions of the stator are optimized and determined via FEA. As a result of the optimization, frequencies of the two working modes are very close to 22 kHz. The major feature of the design is the multi-DOF motion achieved by a single stator.